2016
DOI: 10.1007/s10008-016-3195-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical dissolution of aluminium in electrocoagulation experiments

Abstract: Six experiments are presented to highlight important features of aluminium dissolution when used in electrocoagulation procedure employed to remove oily contaminations from water. First, using a common oil-in-water emulsion: diluted milk, we show that the electrochemically generated coagulant ions are active only in the first few seconds following their generation -hence the electrocoagulation cells' construction should promote the mixing of the nascent Al colloid with the water phase. For this reason the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…Similarly, current densities were 43.96, 32.97, 21.98, 16.48, and 10.99, corresponding to the distance of 1, 2, 3, 4, and 5 cm for S1. Current density reduction with the increase of electrode distance was also observed by Phan et al [20], and further mentioned by Thella et al [21] as a consequence of resistance increase; (ii) the decrease in the electrostatic attraction that caused a slower movement of the generated ions [17] leading to the lower removal efficiency of pollutants since Fekete et al [22] found that the dissolved Al from anode being active as a coagulant for seconds only after its formation; and (iii) the diminution of mass transfer in the reactor [5].…”
Section: Effect Of Electrode Distancementioning
confidence: 56%
“…Similarly, current densities were 43.96, 32.97, 21.98, 16.48, and 10.99, corresponding to the distance of 1, 2, 3, 4, and 5 cm for S1. Current density reduction with the increase of electrode distance was also observed by Phan et al [20], and further mentioned by Thella et al [21] as a consequence of resistance increase; (ii) the decrease in the electrostatic attraction that caused a slower movement of the generated ions [17] leading to the lower removal efficiency of pollutants since Fekete et al [22] found that the dissolved Al from anode being active as a coagulant for seconds only after its formation; and (iii) the diminution of mass transfer in the reactor [5].…”
Section: Effect Of Electrode Distancementioning
confidence: 56%
“…Rather than the relatively steady rise with smoother curves observed in Figure 2, the results showed a much-pronounced zigzag pattern, thus implying an intermittent rise and fall in coagulation activity. In support of this observation, Fekete et al [29] reported that "the released metal ions are only active as coagulants briefly after their formation and should therefore be intermixed as fast as possible." In Table 3, a brief overview of recent studies on electrodes other than Al or Fe utilized in the electrocoagulation of microalgae is compared.…”
Section: Flocculation Efficiency (Fe)mentioning
confidence: 91%
“…In fact, the authors have used different values for the distance between the electrodes. Yilmaz et al [20] worked with 5 mm, Lekhlif et al [29] and Fekete et al [21] used 1 cm, and Fekete et al [21] have tried three values 1, 2, and 3 cm. Khandegar et al have shown that this distance must be sufficiently small for the intensity of the electric field to be sufficient to move the Al 3+ ions produced quickly at the anode towards the solution and large enough to allow sufficient residence of the aluminum hydroxides, so that the flocs are formed [30].…”
Section: Apparatusmentioning
confidence: 99%